A tutela constitucional da exploração de petróleo em águas internacionais em face do princípio do desenvolvimento sustentável: a possibilidade de responsabilização civil do dano futuro - Soares, Pedro Lucas de Moura (2012)
The demands brought by a society doomed to the constant production of global risks, which whose effects are not immediately noticed effects are not perceived immediately, claim from the Law a new Theory about the Risk, that would offer a broad environmental protection, at the same time it would still be compatible with the idea of economic efficiency, required by the Modern Industry. The expansion of the methods and technologies regarding the exploitation and production of oil causes the constant expansion of the exploitable boundaries, especially in ultra-deep waters with the Pre-salt layer, in Brazil, or the still incipient research about the polymetallic nodules and other mineral sources in international waters, like the Atlântico Sudoeste, by the Programme on Ocean Science in Relation do Non Living Resources (OSNLR), a global study performed in partnership with the Intergovernmental Oceanographic Commission, from UNESCO (IOC UNESCO) and also with the Division of Ocean Affairs and Law of the Sea (UNDOALOS). Thus, we aim to analyze the correlation, and possible collisions between the right to a balanced environment and the free exercise of economic activity and the occurrence of environmental damages from the perspective of the exploitation activities of oil and other natural resources in international waters, specifically in the Area, from the constitutional principle of sustainable development and its legitimacy by the environmental international protection. Therefore, this study also aims to evaluate the legal framework for exploration and production of oil in international waters, particularly in the Area, and appraise how the constitutional instruments and mechanisms for environmental protection can impact on the international environmental protection system in order to ensure the present and future generations an ecologically balanced environment, laid down in Article 225 of the Brazilian Constitution, even with so many risks posed by the activities of exploitation and production of oil in international waters. In the meantime, we intend to also intend to investigate the possibility of future liability for environmental damage in order to ensure that constitutional principle and, consequently, and try to define the concept of environmental damage and its implications on the constitutional principle of environmental protection. Given all that was in summary, this work aims to contribute to the evolution of the new Theory of Environmental Risk, turning the law into something more than a punitive or corrective element in this society, but into a legal risk management, that may be triggered even before the consolidation of the damage